2019
DOI: 10.1101/577247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Onchocerciasis-associated epilepsy in the Democratic Republic of Congo: Clinical description and relationship with microfilarial density

Abstract: Background: High epilepsy prevalence and incidence were observed in onchocerciasis-endemic villages in the Democratic Republic of Congo (DRC). We sought to investigate the clinical characteristics of onchocerciasis-associated epilepsy (OAE), and the relationship with microfilarial density. Methods: In October 2017, ivermectin-naive persons with epilepsy (PWE) were recruited from onchocerciasis-endemic areas in the Logo health zone in the DRC. Additional PWE were enrolled in the Aketi health zone, where iverme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Currently, several epidemiological studies have shown a strong relationship between onchocerciasis and epilepsy, including nodding syndrome (NS) [7][8][9][10][11][12][13][14][15][16]. In a meta-analysis investigating the association between onchocerciasis and epilepsy, it was found that for each 10% increase in onchocerciasis prevalence, the prevalence of epilepsy increases on average, by 0.4% [17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several epidemiological studies have shown a strong relationship between onchocerciasis and epilepsy, including nodding syndrome (NS) [7][8][9][10][11][12][13][14][15][16]. In a meta-analysis investigating the association between onchocerciasis and epilepsy, it was found that for each 10% increase in onchocerciasis prevalence, the prevalence of epilepsy increases on average, by 0.4% [17].…”
Section: Introductionmentioning
confidence: 99%